2011
DOI: 10.1007/s10531-011-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the FORAM index in a case of conservation

Abstract: Localized and global impacts are responsible for driving the current decline in coral reef ecosystems. The worldwide debate over the efficacy of Marine Protected Areas (MPAs) as a conservation measure for coral reefs highlights the importance of acquiring accurate indicators of reef resilience and recovery under stressful conditions. Marine benthic foraminifera, considered outstanding indicators for environmental changes, are unicellular eukaryotes that inhabit sandy sediments in coral reefs. There are three k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
10
0
4
Order By: Relevance
“…) that lead to poorer water quality in areas inside the MPAs than outside (Velásquez et al . ). Algae‐dominated reefs have poor productivity and diversity, which translates into the loss of response diversity and functional redundancy vital for ecosystem recovery (Bellwood et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) that lead to poorer water quality in areas inside the MPAs than outside (Velásquez et al . ). Algae‐dominated reefs have poor productivity and diversity, which translates into the loss of response diversity and functional redundancy vital for ecosystem recovery (Bellwood et al .…”
Section: Discussionmentioning
confidence: 97%
“…To determine water quality we used data from the FORAM index by Velazquez et al . (), where FI > 4 indicates an environment conducive to reef growth; 2 < FI < 4 represents the limit for coral growth and unsuitable for recovery; and FI < 2 indicates unfavorable conditions for coral growth (Hallock et al . ; Uthicke et al .…”
Section: Methodsmentioning
confidence: 99%
“…Although the FI can vary with parameters such as distance from the coast (Narayan and Pandolfi, 2010), sediment texture, hydrodynamic regime and light penetration (Barbosa et al, 2009), several studies have demonstrated that the FI is primarily related to water quality (Uthicke and Nobes, 2008;Uthicke et al, 2010;Koukousioura et al, 2011;Velásquez et al, 2011;Reymond et al, 2012;Oliver et al, 2014).…”
Section: Fi and Water Parametersmentioning
confidence: 99%
“…Koukousioura et al (2011) documented the FI at sites in the Aegean Sea, reporting that the FI was 6.8-8.2 in pristine regions and 2.0-3.4 close to sewage outfalls. Velásquez et al (2011) enigmatically found that FIs in a Marine Protected Area (MPA) were lower than in the non-MPA areas sampled, but the difference was attributed to the intense tourism in protected areas. Emrich et al (2017), from work at Caye Caulker, Belize, reported a significant negative correlation between FI and fecal sterols, which they assessed as indicators of sewage pollution.…”
Section: The Foram Index and Its Application To The Maldivesmentioning
confidence: 99%
“…As mentioned, U. tenuifolia face environmental stress factors such as high water temperatures or terrestrial run-offs from rivers such as Magdalena and Sinú (Restrepo et al, 2006;Velásquez et al, 2011). Previously, it has been considered that U. tenuifolia is a susceptible species to bleaching, exhibiting low or negligible recovery after a bleaching (---) P^ of Recruitment and Death.…”
Section: Undaria Tenuifolia: Dominant or Opportunistic?mentioning
confidence: 99%